The Johannine Gospel's concept of community: an intercultural reading - Gharbin, Godibert K. (African Christian studies series, 2025)
The Johannine Gospel's Concept of Community takes an interdisciplinary approach to contextualizing the New Testament in an African milieu, which helps Johannine scholarship intersect with Akan anthropology and sociology through a tripartite frame of interpretation--a narratological analysis of community-oriented narratives in John, the exegesis of the Akan concept of community encapsulated in their proverbial lore (the anthology of inestimable information about the Akan conceptualization of communitarianism), and an engagement between the two conceptual schemes through an intercultural reading. The methodological principles utilized foster a cross-pollination of ideas between the Johannine characterization of a community of God and the community concept present in Akan maxims. This allows the Akan concept of communitarianism to enrich the reader's understanding of the text. It also allows John's theology of community--revealed in what Jesus epitomizes, prescribes, and proscribes for the believing community--to serve as a form of discernible evaluation for Akan (and other) believers on the modus vivendi redolent of a believing community. In the end, it forces a redefinition of community, replacing the anthropocentric, individualistic, and acquisitive elements that have typified the human community with a theocentric and authentically collectivist approach